Processing and analysis of Hi-C data on bacteria - Hofmann, Andreas; Heermann, Dieter W. (Bacterial chromatin, 2018)
The study of three-dimensional genome organization has recently gained much attention in the context of novel techniques for detecting genome-wide contacts using next-generation sequencing. These genome-wide chromosome conformation capture-based methods, such as Hi-C, give a deep topological insight into the architecture of the genome inside the cell. This chapter reviews the steps to process next-generation Hi-C sequencing data to generate a final contact probability map. We describe these steps using publicly available Hi-C datasets of different bacteria. We also present strategies to assess the quality of Hi-C datasets.